Resilience Among Undergraduate Nursing Students in University Malaysia Sabah - Mazlinda Musa; Azra F A; Segaran Ramodran; Marlinah P; Adawiyah N R; Randall M; Syed Sharizman Syed Abdul Rahim; Siti Fatimah Saat (Malaysian Journal of Medicine and Health Sciences, 2020)
Resilience is an important coping mechanism that nurses need to inculcate as they often faced with numerous psychosocial conflicts and stressors in providing day to day patient care. Student nurses are particularly vulnerable to psychosocial stressors and studies indicates that poor resilience is associated with poor academic performance, burn out, depression and high risk of drop out. This study was to examine the level of resilience and associated factors among nursing students in University Malaysia Sabah. Methods: The study entailed a descriptive cross-sectional survey assessing the level of resilience involving student nurses. Ethical clearance for this study was obtained from REC UMS and as well as respondent’s consent. A total of 100(N) nursing students was selected through stratified sampling by year of study (year 1, n=35; year 2 n=35; and year 3 n=30). Sample selection randomization for each year of study was done using full name list generated using Microsoft excel. The study tool consists of a validated instrument (reliability α= 0.82) benchmarked from a previous study which captured respondent`s demo¬graphics and a 28-item inquiry related to resilience. Data analysis use descriptive statistics and Fisher`s-Exact test for correlates. Results: In this study among 100 nursing students 82% (n=82) had high resilience score (cut-off mean score more than 3.5) and 18% low resilience score (cut-off mean score lower than 3.4). Comparing distribution of resilience scores, respondents with low resilience scores were higher among thefirst-year nursing student and stu¬dents of family origin from rural settings. Conclusion: Findings imply that most nursing students in this study have a high level of resilience and a small cohort of the student nurses have low resilience vulnerable to stressors and risk poor achievement and drop out. There is a need to address nursing students with poor resilience and this paper will discuss some pragmatic strategies.